The effect of food service system modifications on staff body mass index in an industrial organization - Hosseini, Reza; Mirghotbi, Mostafa; Pourvali, Katayoun; Kimiagar, Seyed Masoud; Rashidkhani, Bahram; Mirghotbi, Tina (Archives of Advances in Biosciences, 2015)
Due to the adverse effects of obesity and overweight on health status of people, organizations that provide daily food aim for a healthy Body Mass Index among their staff. The purpose of this applied randomized controlled trial (RCT) was to study the effect of modifications in the food service section and nutritional intervention on the BMI of staff in an industrial center. In this applied randomized controlled trial which lasted for 40 days, 116 overweight people (BMI ≥ 26) were randomly selected and divided into control and test groups. Individual daily food plan was prepared by a dietitian and nutritional education sessions were held for test group. At the management level, food menu was modified reduce the calorie intake by at least 1000 Kcal per day for the test group and also cost less for the center. The kitchen staffs were trained to promote healthy cooking and improving the food taste. The satisfaction level of food service was also evaluated before and after the intervention, using a questionnaire. To analyze the findings, SPSS 16 software, independent t-test and paired t-test, and Macnemar test were used. The results showed that BMI in test group decreased from 27.5 ± 2.36 to 26.8 ± 2.15 (p<0.05), while in control group increased by 0.5 Kg/m2. Similar result was observed in weight change. The level of satisfaction of food service following changes in the menu increased significantly in both groups. Also, cost of food and use of fat were reduced by 15% and 8%, respectively. Dietary interventions and improving the nutritional knowledge along with modification in food service system could result in better weight management in organization staff using canteen food.